Trauma and Nostalgia (Amsterdam University Press, 2024)
This volume reflects on the significance of nostalgia in the construction of traumatic pasts, both on an individual and a collective level. By employing an interdisciplinary approach, the volume enhances our understanding of how the entanglements of trauma and nostalgia influence the construction and development of identity. Scholars from a range of academic disciplines and contexts explore the integration of nostalgic memories in discussions of trauma, attending to their interactions in public spaces, patriotic symbolism and rituals, popular culture, cinema, religion, museums, and memorials. The contributors emphasize the role of media and other mass-cultural technologies in disseminating images and narratives related to traumatic and nostalgic experiences. These essays ultimately bring to light the frequently overlooked role of nostalgic longing in shaping the discursive, visual, and material aspects of collective trauma.